La inafectación al Impuesto a la Renta del financiamiento no reembolsable que otorga el fondo de inversiones en telecomunicaciones - Aráoz Villena, Luis Alberto (2013)
Investment in the telecommunications public service is one of the priorities of the Peruvian Administration, especially in those areas of the country in which the placement of capitalis not attractive for entrepreneurs. Now, does the Administration pretend to tax it with the Income Tax? In this article, the authors analyze the Income Tax Law and the assumptions that it establishes, for the purposes of determining if such investment is taxed with this tribute or not.